2023
DOI: 10.18231/j.ijce.2022.041
|View full text |Cite
|
Sign up to set email alerts
|

Non surgical management of a large periapical cyst like lesion using metapex, a three year followup - A case report

Abstract: This case report describes the non - surgical management of a large periapical lesion using Metapex as a intracanal dressing and root canal therapy. Periapical lesions usually develop in non-vital teeth as a result of chronic aggression by the pathogenic microorganisms into the root canal which may appear as radiolucent in periapical radiographs. Treatment of such lesions usually varies from non-surgical and surgical means depending on the individual. In the era of minimally invasive, dentistry, non-surgical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…11 Regular change of metapex as intracanal dressing and root canal therapy has proven to be very beneficial in complete healing of the periapical lesion. 12 Ultrasonic condensation of gutta percha was done for getting a tightly compacted 3 D condensation. Studies done with dye penetration tests reported that ultrasonically condensed gutta-percha mass was more homogeneous with less voids and resulted in a better obturation.…”
Section: Discussionmentioning
confidence: 99%
“…11 Regular change of metapex as intracanal dressing and root canal therapy has proven to be very beneficial in complete healing of the periapical lesion. 12 Ultrasonic condensation of gutta percha was done for getting a tightly compacted 3 D condensation. Studies done with dye penetration tests reported that ultrasonically condensed gutta-percha mass was more homogeneous with less voids and resulted in a better obturation.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaning and shaping with sodium hypochlorite, EDTA, chlorhexidine, warm saline, and Metapex are recommended for infection neutralisation of periapical lesions [ 8 , 9 ]. Metapex is the most successful intracanal medicament for teeth having periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ayodhi et al used Metapex for the healing of large periapical lesions. They concluded that Metapex is very beneficial for the healing of periapical lesions [ 8 ].…”
Section: Discussionmentioning
confidence: 99%